Penerapan Pembelajaran Berdiferensiasi pada Mata Pelajaran Fikih Materi Hukum Halal dan Haram Kelas VI SDN 3 Mantingan Jepara - Fernanda, Natasha Afella; Saefudin, Ahmad (Jurnal Simki Pedagogia, 2025)
Low efforts and difficulties of teachers in motivating students to learn to understand the material, as well as the lack of optimal use of approaches. There are several approaches to creating a creative and interactive classroom atmosphere, namely with differentiated learning. This study aims to explain the application of differentiated learning in fiqh, especially on the material of halal and haram laws in class VI SDN 3 Mantingan Jepara, explain the impact of differentiated learning, and identify the supporters and obstacles of differentiated learning. This study uses a descriptive qualitative research type. Information is obtained from various sources of evidence from interviews, observations, and documentation. After that, the data is reduced, presented, and concluded. The results of the study explain that the differentiation of content, process, product, and learning environment is part of the application of differentiated learning at SDN 3 Mantingan Jepara. Then the impact of the application of differentiated learning in class VI is very effective in improving understanding of the material from student learning outcomes. Finally, the supporting factors of differentiated learning at SDN 3 Mantingan already have facilities such as laptops and projectors for differentiated learning with audio and visual characteristics. In addition, there are obstacles, namely inadequate facilities from the school, so teachers must try to bring projectors and laptops from the office to class, not to mention installing the equipment, and this can take up teaching time.